THE LONGEVITY OF DEMOCRACY: ANALYZING THE CONDITIONS FOR DEMOCRATIC SURVIVAL - Blodgett , Sage E. (Young Scholars Grinchenko – Seton International Journal, 2026)
Three prevalent themes throughout the twenty-first century are weakening democratic institutions, attacks on democracy, and democratic backsliding. There are four key conditions that significantly contribute to why democracies can fail and to maintaining long-term democracy: civic competence and democratic education, media independence and government accountability, management of populist discontent, and participation in international organizations. Using data from Freedom House to compare different regions, the United Nations definition of democracy, and other academic journals, I have researched three states: one representing a democracy under stress, a second representing a democracy currently backsliding, and a third representing a strong, growing democracy. I have also included a case study of complete democratic collapse in the Weimar Republic. My findings indicate the importance of the four conditions in maintaining a long-term democracy.